THE POSITIONING OF STREET NAMES ON EGOCENTRICALLY REFERENCED MAPS: ASSESSMENT OF READING TIME - Rego, Mariana Pereira do; Pugliesi, Edmur Azevedo; Tachibana, Vilma Mayumi (Boletim de Ciências Geodésicas, 2021)
The main objective of this research is to evaluate the reading time of street names on dynamic egocentrically referenced maps for In-Car Route Guidance and Navigation Systems. Two different road network patterns (grid-like or non-grid-like) were considered and tasks were devised to search for street names in two different route segments (where the driver was, or where the driver would have to manoeuvre). Considering a non-grid-like road network pattern, for the task of searching for the name of a road where the driver would manoeuvre, street names aligned horizontally and next to the route were read significantly faster than street names positioned along the route. Street names positioned obliquely required more reading time than street names aligned horizontally. Dynamic maps egocentrically referenced should present street names horizontally aligned and next to the route for the segment related to where the driver will manoeuvre, for both road network patterns. Also, Street names should be positioned next to the car symbol.